EFFECT OF CULTIVARS AND HARVEST DATES ON SOME TRAITS OF YIELD IN RICE - M. K. MohammadAli; J. H. Hamza; A. S. Ahmed (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
A field experiment was carried out at Rice Researches Station in Mashkhab, Najaf in 2020 and 2021 seasons to study the effect of cultivars and harvest date on some traits of rice yield. Randomized complete block design was applied within split-plot with four replications. Five cultivars of rice (Amber 33, Yasmin, Dijlah, Amber-albaraka and Furat 1) were distributed in the main plots and five harvest dates (harvest at physiological maturity and harvest after 7, 14, 21 and 28 days of physiological maturity) in the sub-plots. The results showed significant difference among cultivars, and superiority cultivars of Dijlah, Furat 1 and Yasmin in recording the highest yield due to its superiority in number of grains per panicle or weight of grain. It can be concluded that traits of grain number in panicle and weight of 1000-grain were among the most influential traits in determining the grain yield, and date of harvest plays an active role in determining the traits of yield. Third harvest date was the best in grain yield, and early harvest before that date would cause loss of yield for all cultivars due to the high grain moisture, and delay after that date would cause a loss of yield as a result of shattering ratio of grain, in addition to difference of cultivars in recording shattering ratio according to harvest date. It can be recommended planting cultivars of Dijlah, Furat 1 and Yasmin, as they achieved the highest yield, and considering the harvest date 14 days after physiological maturity the best date to obtain the highest grain yield.